ARCHAIZATION OF A GLOBALIZED SOCIETY IN THE INFORMATION ERA - Орденов, С. С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Introduction. Positive scientific and technical changes, as well as global integration are going on against the background of negative social phenomena. A general move of the global society towards a new social polarization, de-industrialization of a number of countries, rapid increase in unemployment and poverty, widening of the gap between the rich and the poor, and worsening of the ecological situation has been noted recently. These processes correlate with dysfunctional phenomena of deregulation, desocialization, structural imbalance, axiological uncertainty, instability and disequilibrium, which generally correspond to archaization of a globalizing society. The aim and tasks: The aim of the study is to reveal the structural components which give rise to the archaization of a globalizing society in the Information age. Research methods: The research methodology consists of structural-functional, socio-cultural and comparative approaches in their dialectical unity. Research results. The doctrine of the Information or Knowledge society is the product of neoliberalism ideology. The basis of the neoliberal model of global capitalism is the orthodox idea of “self-regulating society” in the form of “impersonal regulation”. However, the world order is influenced by the transnational elite. The latter tries to regulate “self-regulating” social relations through hyper-bureaucratization. The processes of unification, standardization and protocolization of all the spheres of a globalizing society have recently taken the form of a vertically regulated totalitarian monopoly of relations. This fact make them to be on par with such archaic manifestations of the past as absolutism and etatism. Discussion. We turn to the analysis of the neoliberal theories of the post-industrial and Information society in order to compare their basic postulates with the realities of the post-industrial social being. Conclusions. The model of global capitalism ideologically is based on the orthodox idea of a self-regulating society. At the same time, one can see the global introduction of total hyperregulation and the protectionism of the power elites. They use the levers of supranational institutions in favor of big capital-holders. A global world order is formed on these grounds. It accompanied by structural changes in various spheres of public life. The hypertrophication of market relations affects the economy, science, education, politics, government, etc., changing their social status to asocial. In these conditions, information and knowledge are used as tools to promote the ideology of neoliberalism and the destruction of the principle of individual autonomy, as well as for the deliberalization of society. Information and communication technologies themselves turn out to be the means of the new forms of netocracy cyber-elite.